Transformation of Teachers to Mentors: Prerequisite of Time is to Excel Innovative Practices in Academics - Malviya, Neelesh; Malviya, Sapna; Saxena, Rajiv; Dhere, Manisha (Indian Journal of Pharmaceutical Education and Research, 2021)
The perception of Mentoring is definitely not new; indeed, it comes from a character named “Mentor” in Homer’s Odyssey. He was a trusted mentor to Odysseus’ son. The recent studies and Figures have given rise to prosperous mentoring. Mentoring focuses on the individual’s needs, his role is to inculcate and instill skills needed for future roles. Mentors have often had a successful career path, beginning in a similar place as the mentee. They offer assistance through sharing their own experiences, providing valuable feedback and giving the mentee access to their personal network. The technology approaches of teaching and learning are coupled with new techniques viz Case Studies, Student Centered learning, Outcome based learning and problem based learning. Aforesaid approaches are emerged recently and verified to have constructive impact on learning of an individual. Those were the good olden days wherein Professors of the institutes were standing and delivering lecturers via one-way communication, students are listening continuously and preparing their notes, these days are now over and substituted with more innovative and creative ways of facilitating, sharing and disseminating knowledge among the students. The present article summarizes current need of mentors to inculcate skills, nurture talent and build prosperous career of young budding professionals. The highlights of the contents are recent trends of innovative teaching pedagogy to facilitate new breeds and stages of mentoring and its significance in the nation development.
Keywords: Mentor; Teacher; Skills; Teaching pedagogy; Innovation; Knowledge